A brief history of surface‐enhanced Raman spectroscopy and the localized surface plasmon Dedicated to the memory of Richard Van Duyne (1945–2019). (12th November 2020) - Moskovits, Martin; Piorek, Brian D.
Abstract: When discovered in 1977, surface‐enhanced Raman spectroscopy (SERS) almost immediately became a research phenomenon with dozens of groups on many continents probing this unusual result in which the Raman intensity of a molecule could be increased a millionfold when the molecule is placed on rough silver. Multiple putative explanations were reported that were winnowed down to two major groups: one made reference to the erstwhile nearly unknown entity called the surface plasmon (a collective electronic excitation of metal nanostructures); the other argued that SERS is merely unusually intense resonance Raman. The former was first enunciated by Moskovits in 1978. If indeed plasmonic in nature, one might suppose that SERS would be an effect that requires submicroscopic structure (i.e., nanostructure) and that it would be strongest for the coinage and the alkali metals and accordingly predict that the enhancement (which up to that point had been observed only on electrochemically roughened silver) will also be seen for true silver and gold colloids. All of these predictions were rapidly demonstrated experimentally by many groups, and the plasmonic model for SERS has been developed over the past 40 years into a descriptive, predictive, and quantitative theory that accounts for all of the seminal aspects of SERS. Abstract : Surface‐enhanced Raman spectroscopy (SERS) was discovered in 1977. The surface plasmon, a collective electronic excitation, was the major explanation for SERS. The plasmonic model has been developed over the past 40 years into a descriptive, predictive, and quantitative theory that accounts for all of seminal aspects of SERS.